2007
DOI: 10.1007/s11845-007-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity simulation in post-graduate training and assessment: an Irish perspective

Abstract: This study demonstrates successful post-graduate course development in a simulation centre with narrow budgetary restrictions. In addition, it is the first to examine Irish anaesthetists', nurses' and dentists' attitudes towards full-scale simulation as an assessment tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Briefly, it is reasonable to believe that simulators can foster nurses' leadership skills, in the same way that it supports other teamwork abilities (Shapiro et al, 2011), and nurses could use simulation as a test bed in which to explore new clinical models. Next, as with baccalaureate education, integrating simulators in postgraduate nursing curricula may help overcome barriers to throughput (e.g., Langdon & Cunningham, 2007), and relaxing bottlenecks at the undergraduate level (by incorporating simulation there) may also have the secondary effect of providing more candidates for doctoral studies. Finally, simulation-based assessment (perhaps worked into lifelong learning programs) could facilitate the collection of standardized skill across the nursing industry, thereby supporting workforce data collection.…”
Section: (2 5 7 8) Other Recommendationsmentioning
confidence: 99%
“…Briefly, it is reasonable to believe that simulators can foster nurses' leadership skills, in the same way that it supports other teamwork abilities (Shapiro et al, 2011), and nurses could use simulation as a test bed in which to explore new clinical models. Next, as with baccalaureate education, integrating simulators in postgraduate nursing curricula may help overcome barriers to throughput (e.g., Langdon & Cunningham, 2007), and relaxing bottlenecks at the undergraduate level (by incorporating simulation there) may also have the secondary effect of providing more candidates for doctoral studies. Finally, simulation-based assessment (perhaps worked into lifelong learning programs) could facilitate the collection of standardized skill across the nursing industry, thereby supporting workforce data collection.…”
Section: (2 5 7 8) Other Recommendationsmentioning
confidence: 99%
“…Based on various simulation modalities, and a host of clinical presentations, most studies indicate that participants thought that the exercises were realistic and pedagogically useful with respect to clinical training and competency assessment. 119,120 Berkenstadt et al, 91 based on simulations incorporated in the Israeli Board Examination in anesthesiology, reported that those exposed to this form of assessment preferred it to the traditional oral examination. Given that trainees need to demonstrate specific skills, Savoldelli et al 92 also supported the use of simulations as an adjunct to the oral examination for senior anesthesia residents.…”
Section: Assessing the Reliability Of Test Scoresmentioning
confidence: 99%
“…The use of an objective structured clinical examination (OSCE) or mannequin-based simulations for summative assessments has emerged for postgraduate practice and interprofessional training, and their feasibility and acceptability have been demonstrated [ 14 17 ]. However, it is still not routinely used for medical students in EM.…”
Section: Introductionmentioning
confidence: 99%